Strategic Analysis of the Role of Digital Marketing in New Year's Campaigns as an Integrated Approach to Optimize Revenue and Competitiveness of MSMEs - Judijanto, Loso; Suherlan; Jusman, Ikhsan Amar (ADMAN: Journal of Contemporary Administration and Management, 2024)
This study aims to analyze the strategic role of digital marketing in New Year's campaigns as an integrated approach to optimize revenue and competitiveness of Micro, Small, and Medium Enterprises (MSMEs). Digital marketing has become a crucial tool for increasing visibility and consumer interaction, especially during seasonal periods like New Year. By utilizing various digital platforms such as social media, email marketing, and e-commerce, MSMEs can reach a wider market and increase sales. This research employs a literature review with a qualitative approach and descriptive analysis, with data collected from Google Scholar for the 2019-2024 period. The findings indicate that MSMEs leveraging integrated digital marketing, utilizing creative content strategies, influencer marketing, and digital analytics, can optimize the results of their campaigns. The study also provides important implications for MSMEs in designing effective digital marketing campaigns during holiday seasons.